Analysis of Grounding Resistance Value Improvement on 150 kV Glang-Namorambe High Voltage Air Line Tower (SUTT) using three Measurement Points (Three Point Method) - Bastanta Tarigan; Parlin Siagian; Muhammad Erpandi Dalimunthe (Sean Institute, 2025)
Low grounding resistance is an important factor in ensuring the safety and reliability of electric power systems, especially on High Voltage Overhead Lines (SUTT). This study aims to analyze and improve the grounding resistance values on 150 kV SUTT towers on the Glang–Namorambe line using the three-point measurement method. Measurements were conducted to determine the actual condition of the grounding system and evaluate the effectiveness of the improvements made. Initial measurements showed that several towers had resistance values exceeding the maximum PLN standard limit of 10 ohms. To address this, improvements were made by installing additional electrodes, adding conductors, and using ground enhancement materials. After the improvements, remeasurements were conducted for each tower. The analysis results showed that the applied improvement method succeeded in reducing the grounding resistance value significantly, with an average reduction of 40–60%. The final resistance values of all towers were below the specified threshold, so that the grounding system can function properly in protecting equipment and personnel safety from overvoltage disturbances caused by lightning and ground faults.